PRECISE ECLOGITIZATION AGES DEDUCED FROM RB/SR MINERAL SYSTEMATICS: THE MAKSYUTOV COMPLEX, SOUTHERN URALS, RUSSIA - Glodny J.; Bingen B.; Austrheim H.; Molina J.F.; Rusin A. (My University, 2002)
The Maksyutov complex (Southern Urals, Russia) is a well-preserved example of subduction-related high-pressure metamorphism. One of its two litho-tectonic units consists of rocks that experienced eclogite-facies conditions. Published 40Ar/39Ar data on phengite, U/Pb data on rutile, and Sm/Nd mineral data define a cluster of ages around 370 to 380 Ma. Nevertheless, no consensus exists as to the detailed interpretation of data and the exact age of eclogitization. We present new, high-precision internal mineral Rb/Sr isochrons for eclogite-facies metabasites, felsic eclogites, and eclogite-facies quartz veins. Nine isochrons, mainly controlled by omphacite and white mica phases, give concordant ages with an average value of 375 ± 2 Ma (2σ). Microtextural features, such as prograde growth zoning in eclogite-facies phases, suggest that the assemblages dated formed at a stage of prograde metamorphism. Sr-isotopic equilibria among eclogite-facies phases, and among eclogite-facies fluid veins and the host rocks, indicate that our ages reflect crystallization ages, related to the prograde-metamorphic, probably fluid-mediated eclogitization reactions. This interpretation is reinforced by data from fluid-precipitated quartzitic eclogites, whose modal composition, together with intergrowth relationships, conclusively imply closed-system behavior after crystallization. The possible occurrence of a pre-375 Ma event of ultra-high-pressure metamorphism (UHPM) in the Maksyutov complex is disproved by isotope systematics, microtextures, and mineral zoning patterns.